Analysis of Consumer Behavior in Choosing Quality Imported Used Goods - Widianti, Wiwin; Sikki, Nurhaeni; Guterres, Alexandre de Sousa (Sinergi International Journal of Management and Business, 2024)
This research is entitled "Analysis of Consumer Behavior in Choosing Imported Quality Used Goods". The aim of this research is to find out how consumers behave in choosing imported quality used goods, to find out the quality of imported quality used goods and to find out how traders maintain consumers' buying interest in choosing imported quality used goods. This research uses qualitative research using a descriptive approach, by conducting observations, interviews and documentation. The results of this research show that consumer behavior in choosing imported quality used goods is influenced by various factors, including the price of the goods being sold is relatively cheap, the quality of the goods is still good and suitable for use, there are many types of goods to choose from, and this is one of the factors in choosing used clothes at the Cimol Gedebage market. The results of this questionnaire interview show that the quality of imported used goods has good material quality, although not 100%, but in terms of suitability it is still very suitable for use. The results of this interview questionnaire are that several used goods sellers at the Cimol Gedebage market will first approach their consumers so that they feel comfortable and want to buy goods from the shop again.